2017
DOI: 10.1186/s13195-016-0231-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral apoE isoform levels in cognitively normal APOE ε3/ε4 individuals are associated with regional gray matter volume and cerebral glucose metabolism

Abstract: Background: Carriers of the APOE ε4 allele are at increased risk of developing Alzheimer's disease (AD), and have been shown to have reduced cerebral metabolic rate of glucose (CMRgl) in the same brain areas frequently affected in AD. These individuals also exhibit reduced plasma levels of apolipoprotein E (apoE) attributed to a specific decrease in the apoE4 isoform as determined by quantification of individual apoE isoforms in APOE ε4 heterozygotes. Whether low plasma apoE levels are associated with structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 52 publications
(64 reference statements)
7
50
1
Order By: Relevance
“…A majority of AD brains show CAA, which is a result of amyloid deposition within the walls of small vessels in the leptomeninges and brain parenchyma. A recent study from Nielsen et al ( 2017 ) showed increased incidence of CAA in ApoE4 postmortem brain tissues. Interestingly, they also found an association with E2, but this finding is not consistent across other studies (Rannikmae et al, 2014 ).…”
Section: Apoe Cerebral Blood Flow and Cerebral Amyloid Angmentioning
confidence: 92%
See 2 more Smart Citations
“…A majority of AD brains show CAA, which is a result of amyloid deposition within the walls of small vessels in the leptomeninges and brain parenchyma. A recent study from Nielsen et al ( 2017 ) showed increased incidence of CAA in ApoE4 postmortem brain tissues. Interestingly, they also found an association with E2, but this finding is not consistent across other studies (Rannikmae et al, 2014 ).…”
Section: Apoe Cerebral Blood Flow and Cerebral Amyloid Angmentioning
confidence: 92%
“…In the same study, higher ratios of apoE4/apoE3 were negatively associated with CMRglc and GMV. These results may point toward an important role for peripheral apoE levels in modulating brain health and may offer insight into the higher risk of AD in women, particularly women with E4 (Altmann et al, 2014 ; Nielsen et al, 2017 ).…”
Section: Apoe Cerebral Glucose Metabolism and Peripheral mentioning
confidence: 95%
See 1 more Smart Citation
“…We found that APOE ɛ 4 carriers again demonstrate mild glucose hypometabolism in brain areas associated with AD when compared to the normative NeuroStat database; furthermore, subjective memory complainers (but not non-complainers) also showed a pattern of glucose hypometabolism [ 54 ]. Furthermore, it has been suggested that plasma apoE levels are age- and sex-dependent, and that brain regional glucose usage and grey matter volume correlate with peripheral apoE levels, as well as cognitive performance [ 55 ]. This is further evidence of AD being a systemic condition, and that a pre-clinical peripheral biomarker panel is an achievable objective.…”
Section: Early Stepsmentioning
confidence: 99%
“…Several studies have looked at brain regions that impact AD prognosis. In univariate studies about AD prodromal stages, differences between MCI converters and non-converters have been identified to be localised mainly in the right temporoparietal and in the medial frontal area (Chételat et al, 2003 , 2005 ; Drzezga et al, 2003 ; Nielsen et al, 2017 ). More precisely, according to the regions defined by the AAL atlas, the regions that are the most often identified as relevant for AD conversion are the superior temporal, the inferior parietal and the superior medial frontal.…”
Section: Resultsmentioning
confidence: 99%